2003
DOI: 10.1021/jf020832b
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Green Coffee Protein Profiles during Roasting

Abstract: To reveal its flavor, coffee has to be roasted. In fact, the green coffee bean contains all ingredients necessary for the later development of coffee flavor. It is now widely accepted that free amino acids and peptides are required for the generation of coffee aroma. However, the mechanisms leading to defined mixtures of free amino acids and peptides remain unknown. Information pertaining to the identification of precursor proteins is also lacking. To answer some of these questions, two-dimensional polyacrylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 37 publications
3
77
0
4
Order By: Relevance
“…This change in the microstructure helps to create the desired crunchiness of roasted peanuts and may have potential as a marker for textural properties [39] and has been shown to decrease the force required to compress peanuts after roasting [40]. Similar results have been observed in other oilseeds such as almonds, hazelnuts, and cashews, which indicate that long roasting times decreases moisture content and increases crunchiness [41][42][43]. High roasting temperatures have also been reported to decrease the amount of force needed to compress nuts [40].…”
Section: Optimization Of Process Variables and Modelingsupporting
confidence: 54%
“…This change in the microstructure helps to create the desired crunchiness of roasted peanuts and may have potential as a marker for textural properties [39] and has been shown to decrease the force required to compress peanuts after roasting [40]. Similar results have been observed in other oilseeds such as almonds, hazelnuts, and cashews, which indicate that long roasting times decreases moisture content and increases crunchiness [41][42][43]. High roasting temperatures have also been reported to decrease the amount of force needed to compress nuts [40].…”
Section: Optimization Of Process Variables and Modelingsupporting
confidence: 54%
“…The SDS-PAGE profile of extracted proteins changes drastically from green to roasted coffee. It was shown that, during the roasting process, the water soluble proteins are highly transformed, especially the 11S storage proteins (Nunes and Coimbra 2001;Nunes and Coimbra 2002a, b;Montavon et al 2003). The change in the water soluble protein SDS-PAGE profile observed during the roasting process is similar to what is observed when oxidized chlorogenic acids are reacted with the green coffee 11S storage protein in model systems (Montavon et al 2003;Rawel et al 2005).…”
Section: Role Of Hydroxycinnamates In Melanoidin Formationmentioning
confidence: 79%
“…The aerobic incubation of the coffee seed suspensions results in the oxidation of the chlorogenic acid and further triggers the fragmentation or digestion of the coffee seed storage protein resulting in a release of free amino acids and peptides (Montavon et al 2003a). Observations during the roasting of coffee beans suggest that besides the contribution of the released amino components, polyphenols bound to subunits of the storage protein may also contribute to the characteristic generation of the coffee aroma (Montavon et al 2003b). Both examples illustrate the modification of proteins by chlorogenic acid, which can take place during growing, maturation and processing of phenol containing food sources.…”
Section: Reactions With Amino Acids and Proteinsmentioning
confidence: 99%